Subaqual soils of Antarctica: conditions of formation and perspectives of microbiological research - D. A. Nikitin; M. V. Semenov (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
The relevance of polar research is constantly increasing due to the higher response of Arctic and Antarctic ecosystems to global climate warming compared to other areas of the planet. The increase in average annual temperatures leads to the melting of glaciers, inundation of a part of the territory and, consequently, to the expansion of areas of subaqual (underwater) precipitation. In recent years, there has been a significant increase in the number of studies in which underwater soils are not only recognized as objects of soil science, but are also considered as full-fledged components of the soil cover of the planet. The sustainable existence of soils and ecosystems in Antarctica becomes possible only in local erosion bases – lakes, where biota is oftenly represented only by microorganisms. Biota activity results in the transformation of geological rocks in situ and accumulation of significant organic matter stock. Microbiome seems to be a determining factor of soil formation, namely in subaqueous Antarctic biotopes, which are characterized by all the elementary processes of soil formation in reducing and, often, anaerobic conditions. Nevertheless, quantitative parameters of their microbiome (biomass, cell counts, number of ribosomal genes of prokaryotes and fungi, basal respiration) are still unknown for subaqual soils of Antarctica, although these parameters are necessary for evaluation of ecosystem productivity, including the intensity of the C cycle and biological activity of soil. This review examines the current state of research on microbial communities in Antarctic biotopes, discusses the role of microorganisms in soil formation processes of subaqual soils in Antarctica, and explains the need for microbiological studies of this soil type.